Interactions between the tillage system and crop rotation on the crop yield and weed populations under arid conditions. Issue 3 (9th May 2014) - Sarani, Mansoor; Oveisi, Mostafa; Mashhadi, Hamid Rahimian; Alizade, Hassan; Gonzalez‐Andujar, Jose Luise
<x xml:space="preserve">Abstract</x> Field experiments were conducted in Iran in order to determine the interactions between the tillage system and crop rotation on weed seedling populations and crop yields from 2002 to 2005. No tillage, shallow tillage and deep tillage were the main plots and three crop sequences comprising continuous wheat (W‐W), wheat–canola–wheat–canola (C‐W) and wheat–safflower–wheat–safflower (S‐W) were the subplots. Bromus japonicus, Carthumus lanatus, Polygonum aviculare, Lolium temulentum and Avena ludoviciana were found to be the dominant species. The initial weed population in 2002 was estimated at 65 seedlings per m2 and B. japonicus (∼35 seedlings per m2) was the most abundant species, followed by A. ludoviciana and L. temulentum. The dominant weed species mostly did not favor the combination of S‐W and C‐W with any tillage type. For the B. japonicus population, S‐W in combination with moldboard plowing indicated the lowest seedling population. In conclusion, the crop sequence in combination with tillage would help to control troublesome weed species. Safflower and canola were determined to be effective in reducing the grass weeds. The inclusion of these crops in rotation also increased the total revenue of the cropping systems because of the higher sale price of canola and safflower.